Memory, Identity, and Amnesia in Kazuo Ishiguro's The Buried Giant: A Cultural Memory Analysis through Jan and Aleida Assmann's Theories - Jamali, Noshin; Motiee, Mohammad; Ebrahimi, Seyed Reza (Assessment and Practice in Educational Sciences, 2024)
A post-Arthurian Britain engulfed in communal forgetfulness serves as the setting for Kazuo Ishiguro's The Buried Giant, which deftly examines the intertwined themes of memory, identity, and amnesia. The story explores the complex relationship between cultural narratives and human memory via the journey of Axl and Beatrice, an elderly couple traversing a fog of amnesia. This study explores how forced forgetting serves as a survival strategy and an instrument of power, causing society disintegration and sustaining cycles of animosity, drawing on the theories of cultural memory developed by Jan and Aleida Assmann. The conflict between personal memories and group forgetfulness, the influence of cultural memory on character identities, and the effects of censored historical narratives on social cohesiveness are some of the main study concerns. The results show that remembering and forgetting play a crucial role in the development of both personal and societal identities. In a world where selective historical amnesia is a problem, Axl and Beatrice's hunt for their missing kid serves as a metaphor for their quest for shattered identities. In order to preserve the tenuous peace between the Saxons and Britons, the mist, which represents forced amnesia, hides unpleasant facts while undermining ties to the community and genuine reconciliation. Wistan's quest to unearth hidden historical facts highlights the conflict between identity, pain, and power. The book concludes by arguing that communal memory is essential to promoting healing and reconciliation and criticizing the morality of forgetting as a peacemaking strategy. This research shows how Ishiguro's work is still relevant today for comprehending the intricacies of historical narratives and identity building by placing it within larger discourses on memory studies.